Learning and collaboration technologies : designing learning experiences : 6th International Conference, LCT 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, Proceedings.: designing learning experiences : 6th International Conference, LCT 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, Proceedings. Part I (2019) - Unknown
No abstract available